Sexual Dysfunctions in Patients Receiving Opioid Agonist Treatment and Heroin-Assisted Treatment Compared to Patients in Private Practice—Identifying Group Differences and Predictors - Meyer, Maximilian; Brunner, Patrick; Geissmann, Leonie; Gürtler, Martin; Schwager, Fabienne; Waldis, Rowena; Vogel, Marc; Wiesbeck, Gerhard A.; Dürsteler, Kenneth M. (Frontiers in Psychiatry, 2022)
Background and Aims: Sexual dysfunctions (SDs) show a marked impact on a person’s general well-being. Several risk-factors like physical and mental illnesses as well as alcohol and tobacco use have to date been identified to contribute to the occurrence of SDs. The impact of opioid-agonist treatment (OAT) on SDs remains unclear, with some studies demonstrating an improvement after methadone maintenance treatment (MMT) initiation. However, no studies on the prevalence and predictors of SDs in heroin-assisted treatment (HAT) exist to date. Methods: A cross-sectional study was conducted with patients from a MMT centre (n=57) and a centre specialising in HAT (n=47). A control group of patients with mild transient illnesses (n=67) was recruited from a general practitioner (GP). The International Index of Erectile Function, the Female Sexual Function Index, as well as measurements for psychological distress, depressive state, nicotine dependence, and high-risk alcohol use were employed. Patients also completed a self-designed questionnaire on help-seeking behaviour regarding sexual health. Mann-Whitney-U tests and chi-square tests were performed for group comparisons and binary logistic regression models were calculated. Results: Twenty-five percent of the GP sample (n=17), 70.2% (n=40) of the MMT sample, and 57.4% (n=27) of the HAT sample suffered from SDs at the time of study conduction. OAT patients differed significantly from GP patients in depressive state, high-risk alcohol use, nicotine dependence, and psychological distress. Age, depressive state, and opioid dependence predicted the occurrence of SDs in the total sample. No differences between OAT and GP patients were found regarding help-seeking behaviour. Discussion: Age, depressive state, and opioid dependence predicted the occurrence of SDs in the total sample. It remains unclear whether SDs are caused by opioid intake itself or result from other substance-use related lifestyle factors, that were not controlled for in this study. A lack of help-seeking behaviour was observed in our sample, underlining the importance of clinicians proactively inquiring about the sexual health of their patients. Conclusion: The high prevalence of SDs observed in MMT does not differ from the prevalence in HAT. Clinicians should actively inquire about their patients’ sexual health in GP and OAT centres alike.